IMPLEMENTATION OF RELIGIOUS AND HUMANITARIAN VALUES STRATEGY BASED ON TRI HITA KIRANA (THK) FOR EMPLOYEES PT. JNE ROGOJAMPI DISTRICT - Mubarok, M. Khusni; Syakur, Abd.; Achmad Budi Susilo, Tri; Dicky Riza, Moch; Fatima, Siti (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2024)
This service aims to find out the implementation of the Religious Values and Humanitarian Values Strategy in THK in various aspects at the company PT. JNE. This service also uses the Socialization method, designing a simulation regarding service utilization, Testing the results of a technical design on how to serve a THK based customer. Implementation is already in PT policy. JNE which has religious and human values at THK includes: the existence of a tangible company, reliable in accommodating consumers, fast response in responding to consumer complaints, insurance for employees and consumers and empathy for consumers which indicates maintaining the existence of the company's relationship with society at large. by serving wholeheartedly and best for the blessing of God.